MRI-guided intracerebral convection-enhanced injection of gliotoxins to induce focal demyelination in swine - Kalkowski, Lukasz (PLoS One, 2018)
Demyelinating disorders such as multiple sclerosis (MS) or transverse myelitis are devastating neurological conditions with no effective cure. Prevention of myelin loss or restoration of myelin are key for successful therapy. To investigate the disease and develop cures animal models with good clinical relevance are essential. The goal of the current study was to establish a model of focal demyelination in the brain of domestic pig using MRI-guided gliotoxin delivery. The rationale for developing a new myelin disease model in the domestic pig was based on the fact that the brain in pigs is anatomically and histologically much more similar to that of humans compared to the rodent brain. For MRI-assisted gliotoxin injection, eight 30 kg pigs were subjected to treatment with lysolecithin (20, 30 mg/ml); or with ethidium bromide (0.0125, 0.05, 0.2 mg/ml). Animals were placed in an MRI scanner for intraparenchymal targeting of gliotoxin into the corona radiata (250 μl over 1h), with real-time monitoring of toxin distribution on T1 scans and monitoring of lesion evolution over seven days using both T1 and T2 scans. After the last MRI, animals were transcardially perfused and brains were processed for histological and immunofluorescent analysis. Gadolinium-enhanced T1 MRI during injection demonstrated biodistribution of the contrast (as a surrogate marker for toxin distribution) and its diffusion through the brain parenchyma. Lesion induction was confirmed on T2-weighted MRI and histopathology, thus enabling the establishment of optimal doses of gliotoxins. To conclude, MRI-guided focal demyelination in swine is accurate and provides real-time confirmation of gliotoxin, thus facilitating placement of focal lesions with high precision. This new model of focal demyelination can be used for further investigation and development of novel therapeutic approaches.